Methodology for using forsight technology in training future ecologists in Uzbekistan - Rakhimov Oktyabr; Rakhimova Dilrabo; Ashurova Laylo; Khujakulov Abdulaziz (E3S Web of Conferences, 2023)
Foresight is one of the most modern technologies of environmental forecasting, and it is a relatively new technology in the conditions of Uzbekistan. In developed countries, eco-foresight is widely used in predicting the consequences of environmental problems and crises, but the theory, practice, and methodology of its use in the educational process have not been fully developed. Foresight studies and projects implemented by the authors in the international education system were analyzed. In the process of training future ecologists, the methodology of using foresight technology in the teaching of specialized subjects has been developed. According to this methodology, the use of the forosite in training sessions is divided into 3 blocks: preparation for training, organization of lectures and practical exercises using the foresite technology, and blocks of independent education. The development of “Eco-foresight competence” in future managers is based on the implementation of training sessions using foresight methods, the author's definition of foresight competence and competence is given